Clinical Biomarkers and Pathogenic-Related Cytokines in Rheumatoid Arthritis - Xiaoyin Niu; Guangjie Chen (Journal of Immunology Research)
Rheumatoid arthritis (RA) is a common autoimmune disease with unknown etiology and pathogenesis. Although major therapeutic advances have been made in recent years, there is no cure for the disease. Current medications mainly reduce inflammation in order to relieve pain and slow joint damage, but many have potentially serious side effects. Therefore, to find specific biomarkers will benefit both RA patients to find relief from the disease and physicians to monitor the disease development. A number of biomarkers have been discovered and used clinically, and others are still under investigation. The autoantibodies, which are widely used in diagnosis and prognosis, novel biomarkers, which reflect clinical disease activity, and newly found biomarkers and pathogenic-related cytokines are discussed in this review.